2017
DOI: 10.24171/j.phrp.2017.8.6.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Blood Pressure and Arterial Stiffness in Middle-Aged Korean Women

Abstract: ObjectivesOur study aims to provide basic scientific data on the importance of obesity management in middle-aged Korean women by analyzing its effects on blood pressure and arterial stiffness. In addition, we examined the correlations of these two parameters.MethodsThe study participants were 40 middle-aged female volunteers, who were classified into obesity group (n = 20) and normal weight group (n = 20). Statistical analysis was performed using independent t-test and the Pearson correlation coefficient was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
3
7
0
1
Order By: Relevance
“…Interestingly, it was observed that in the more obese group, the diastolic pressure increases more ( p < 0.001) than systolic pressure as compared to the less obese group (e.g., mean 24-h systolic pressure was higher in group 2 by 5 mmHg as compared to group 1, and diastolic pressure by as much as 9 mmHg). A similar association, additionally correlated with increased vessel stiffness in such patients, was reported by Korean authors, though their patient group was rather small [ 18 ]. Unlike in our study, according to the paper by Higgins et al of 1988, based on the Framingham study, greater body weight was associated with increased systolic and diastolic pressure proportionally to baseline—patients with the upper quintile values of BMI demonstrated higher systolic pressure by 16 mmHg and higher diastolic pressure by 9 mmHg as compared to patients with the lowest quintile values of BMI [ 19 ].…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, it was observed that in the more obese group, the diastolic pressure increases more ( p < 0.001) than systolic pressure as compared to the less obese group (e.g., mean 24-h systolic pressure was higher in group 2 by 5 mmHg as compared to group 1, and diastolic pressure by as much as 9 mmHg). A similar association, additionally correlated with increased vessel stiffness in such patients, was reported by Korean authors, though their patient group was rather small [ 18 ]. Unlike in our study, according to the paper by Higgins et al of 1988, based on the Framingham study, greater body weight was associated with increased systolic and diastolic pressure proportionally to baseline—patients with the upper quintile values of BMI demonstrated higher systolic pressure by 16 mmHg and higher diastolic pressure by 9 mmHg as compared to patients with the lowest quintile values of BMI [ 19 ].…”
Section: Discussionsupporting
confidence: 80%
“…In our study, the obese show an increase in SBP, DBP and MAP with a return to baseline values at the end of surgery. These results are in accordance with those of preceding studies, which demonstrate that obesity is closely related to blood pressure [19].…”
Section: Discussionsupporting
confidence: 94%
“…24 Numerous studies have examined associations between individual components of LS7 and arterial stiffness. They have reported significant and generally consistent positive associations between central arterial stiffness and diabetes and prediabetes, 25,26 obesity, 27,28 physical inactivity, 6,29,30 high BP, 31 total cholesterol, 32 and dyslipidemia. 33 The relation between smoking and arterial stiffness might be dependent on the anatomic segment of the vascular tree assessed.…”
Section: Discussionmentioning
confidence: 93%